TRANSFORMATION OF ENERGY BASE IN POLAND. ENERGY CON-SERVATION AND USE OF RENEWABLE ENERGY - Bondarenko, Taras (Forestry, Forest, Paper and Woodworking Industry, 2024)
The article is about the energy transformation of the Polish economy over the last 25 years. The basic steps of transformation, mechanisms of white certificates, energy audits, energy conservation processes in the industry. Also, the article focuses on the use of renewable energy sources in Poland, such as biomass, hydropower engineering, wind power engineering, etc., as well as mechanisms for financing projects in the field